Estimation of Carbon Reserved in Mangrove Forest at the Estuary of the Batang Apar River, North Pariaman District, Pariaman City, West Sumatra Province - Yossie Amanda; Aras Mulyadi; Yusni Ikhwan Siregar (Ilmu Perairan (Aquatic Science), 2021)
This study was conducted in March 2020 located in Muara Sungai Batang Apar North Pariaman District Pariaman City of West Sumatra Province. The aimed of the study is to find out the amount of density, biomass, carbon stock and CO2 uptake, as well as to know the relationship of density with biomass, carbon stocks and CO2 uptake. The method used in this study is a method of surveying and analyzing samples conducted in the Marine Chemistry Laboratory of the Department of Marine Sciences Faculty of Fisheries and Marine, Riau University. The average number of mangrove upright densities in the study area at all three stations was 1.407,41 ind/ha, the average amount of mangrove biomass is 666,97 tons/ha, the average amount of mangrove carbon stock is 313,52 tons/ha, the average amount of soil carbon stock is 2.561,90 tons/ha and the average amount of CO2 uptake is 1.149,56 tons/ha.